The Use of Songs and Movement in Teaching Arabic for Early Grade Learners at Islamic Elementary Schools: A Systematic Literature Review - Mahmudah, Mahmudah (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
Teaching Arabic to early grade students presents unique challenges, particularly in fostering motivation and building basic vocabulary. Learning media that combine elements of music and physical movement are considered promising in addressing these challenges, particularly in primary education, which emphasizes a multisensory approach. This study aims to systematically review the literature on the use of songs and movements as a medium for teaching Arabic in primary schools. A Systematic Literature Review (SLR) approach was used, guided by the PRISMA protocol, with sources drawn from Sinta and Scopus indexed journals published between 2015 and 2025. This study systematically reviewed 35 empirical studies exploring the impact of songs and movements on teaching Arabic to early grade learners. Analysis of the 35 selected articles revealed that integrating songs and movements consistently increased student engagement, accelerated vocabulary acquisition, and strengthened memory retention through auditory and kinesthetic stimulation. The effectiveness of this approach was influenced by teacher involvement, availability of learning media, and alignment with student characteristics. Theoretically, this study strengthens the relevance of multisensory strategies in language teaching. Future research is recommended to test the effectiveness of this method through a more controlled experimental design.